Pengaruh Label Halal dan Ketersediaan Produk Terhadap Keputusan Pembelian Konsumen pada 212 Mart di Kota Medan - Rini Astuti; M. Ali Hakim (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purpose of this study was to determine the effect of halal labels and product availability on the purchase decision of 212 mart in Medan city. The approach used in this research is associative with the type of data used is quantitative data. The population in this study were all 212 mart consumers in Medan city and the samples used were 100 people using probability sampling. This study uses data collection techniques, namely questionnaire, interview, and documentation. Data analysis techniques in this study used multiple linear regression. It is known that the halal label has a significant effect on purchasing decisions at 212 marts in Medan city. It is known that the availability of products has a significant effect on purchasing decisions at 212 marts in Medan city. Simultaneously known halal labels and product availability significantly influence purchasing decisions at 212 mart in Medan.